Dynamic Transparency, Prudential Justice, and Corporate Transformation: Becoming Socially Responsible in the Internet Age - Madsen, Peter (Journal of business ethics, 2009)
This article brings together two concepts of ethical practice into a single construct that describes how modern corporations can responsibly meet the information needs of their stakeholder networks in a way that promotes both corporate self-interest and widespread distributive justice. Internet technology is providing corporations with transformative tools that permit and encourage the exercise of social responsibility through “dynamic transparency.” “Prudential justice” is a concept representing a set of values that can provide an ethical justification for corporate implementation of dynamic transparency. This article argues that by using dynamic transparency in accordance with the provisions of prudential justice, firms can avoid many crises and manipulative or deceptive information transfers, can fulfill their responsibilities regarding stakeholders’ informational rights, and can undergo an organizational culture transformation that allows them to move from pure corporate egoism to a beneficial mix of self-interest and corporate social responsibility.